Code-Switching Patterns of English Teachers in an Indonesian Preschool Context: A Case Study at TK Essential Education Bengkulu - Eki Saputra (CV. Mitkom Indotama, 2026)
This study investigates the patterns and functions of code-switching (CS) employed by English teachers in an Indonesian preschool setting. In the complex linguistic landscape of Bengkulu, where students navigate multiple local dialects alongside the national language, code-switching serves as a vital pedagogical bridge. The present study is a qualitative case study conducted at TK Essential Education Bengkulu during the 2025/2026 academic year. It was designed to explore how teachers utilize tag-switching, inter-sentential, and intra-sentential switching to maximize a restricted 30-minute instructional window for students with zero prior English exposure. The results revealed that: (1) code-switching is a deliberate scaffolding tool that ensures comprehension and maintains emotional security; (2) inter-sentential switching dominates classroom management, while intra-sentential switching is primarily used for vocabulary building; and (3) the integration of local codes (Melayu Bengkulu, Serawai, Rejang) prevents